1976
DOI: 10.3109/10826087109045526
|View full text |Cite
|
Sign up to set email alerts
|

Graduates and Splitees from Therapeutic Community Drug Treatment Programs: A Comparison

Abstract: As greater numbers of drug abusers seek treatment and drug rehabilitation program resources become more and more scarce, selection processes should become based on scientific research rather than on the intuition of a few influential personnel. Many therapeutic community drug treatment programs have a preferential policy for accepting voluntary over court-ordered commitments. Our findings indicate that such a policy discriminates against those individuals who are most likely to succeed in completing their trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
0
1

Year Published

1981
1981
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(14 citation statements)
references
References 15 publications
2
11
0
1
Order By: Relevance
“…Consistent with prior research among public populations and therapeutic communities (Aron and Daily, 1976;Beckman and Bardsley, 1986;Kingree, 1995), our results from a private, managed care population suggest that predictors of retention are sex specific. Although women and men shared one general pattern (i.e., the prediction of retention by fewer and less severe drug problems), other predictors were sex specific.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with prior research among public populations and therapeutic communities (Aron and Daily, 1976;Beckman and Bardsley, 1986;Kingree, 1995), our results from a private, managed care population suggest that predictors of retention are sex specific. Although women and men shared one general pattern (i.e., the prediction of retention by fewer and less severe drug problems), other predictors were sex specific.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have examined the predictors of retention in substance abuse treatment programs, but most have focused on retention in therapeutic communities (Aron and Daily, 1976;Condelli, 1994;De Leon et al, 1997), have been limited to homeless or other public treatment populations (De Leon et al, 1997;Kingree, 1995;McCusker et al, 1995;Westreich et al, 1997), or have used samples with few or no women (Altman et al, 1978;De Leon et al, 1997;Roffe, 1981;Westreich et al, 1997). Little is known about factors that influence treatment retention in an insured population, particularly a managed care population, A few studies have suggested that the factors which influence treatment retention may differ for women and men (Aron and Daily, 1976;Beckman and Bardsley, 1986;Kingree, 1995); only one (Kingree, 1995) is recent, and it examined a public population.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The primary substance of abuse may also be important, although this varies across studies and substances (e.g., Condelli & Dunteman, 1993;De Leon et al, 1997;Ravndal & Vaglum, 1994;Williams & Roberts, 1991). Drug abuse history (type of drug most identified with, length of abuse, intravenous use, and size of habit) is also related to whether clients complete treatment (Aron & Daily, 1976;Condelli & De Leon, 1993).…”
mentioning
confidence: 99%
“…Los primeros trabajos sobre adhesión al tratamiento en programas para drogodependientes, con pacientes ingresados en una comunidad terapéutica, fueron realizados a mediados y finales de los años setenta (Wexler y De Leon, 1977;Aron y Daily, 1976). Los resultados de estos estudios sugieren que los sujetos que abandonan suelen tener un problema más grave en cuanto al trastorno adictivo y la psicopatología asociada que los que permanecen y finalizan los tratamientos (Secades y Fernández-Hermida, 2000).…”
unclassified